The benefit of interleaved presentation in category learning is independent of working memory. Issue 2 (7th February 2020) - Wang, Jiawei; Liu, Zhiya; Xing, Qiang; Seger, Carol A.
ABSTRACT: We tested whether working memory (WM) resources were necessary for the interleaved presentation benefit over blocked presentation in category learning. We examined category learning in the Kornell and Bjork [2008. Learning concepts and categories: Is spacing the "enemy of induction"? Psychological Science, 19 (6), 585] artistic style task while participants performed the numerical Stroop task as a dual task in order to interfere with WM maintenance and WM dependent executive functions. In addition, we evaluated whether individual differences in WM capacity (WMC), assessed via complex span tasks, would affect learning. The results revealed a superiority for interleaved presentation in both single-task and dual-task conditions, as well as superior performance for participants with relatively high WMC. Importantly, there was no interaction between the presence of the dual task and interleaving, or WMC and interleaving, indicating that the benefits of interleaving are independent of WM. We also probed participants' metacognitive judgments about whether blocking or interleaving was superior for learning, and found that most participants reported blocking was more effective, contrary to the reality that interleaving led to the best performance. These results support theories of the interleaving effect that are independent of working memory resources and pose a challenge to theories that rely on working memory mediated comparisons of items across trials.